Should you "picture" this? Effects of picture-taking features of food diary apps on memory, liking, and wanting. (1st January 2022) - Bayliss, Lauren; Wu, Linwan
Abstract: Picture-taking functions are commonly available features in food diaries and other mobile applications that may influence how we think about the very food we consume. Because memories of food (Higgs & Donohoe, 2011) and the act of recording food consumption (Turk et al., 2013) have been shown to influence desire for and consumption of food, this paper investigated the effects of using the picture-taking feature of a food diary app on liking, wanting, and memory of food. Using a simple food diary app with a picture-taking feature loaded onto iPads, participants took part in a lab experiment where they either did or did not use the picture-taking feature of the app as they ate a snack. To capture the changes in liking and wanting that naturally occur as more food is consumed, participants were also randomly assigned to receive either larger or smaller portions of the snack. The results indicate that picture-taking while eating is associated with greater wanting of the food following consumption. Furthermore, for smaller portions of food, taking pictures during consumption is associated with greater liking of the food. However, taking pictures in the smaller portion size condition was also associated with less detailed recall of food's sensory properties.